2011
DOI: 10.1177/0020764011415595
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of family work interventions on schizophrenia: Evidence from a multicentre study in Catalonia

Abstract: This is the first study to explore the effectiveness of family intervention in a high-expressed emotion context in Catalonia. The findings add weight to the growing literature supporting these interventions in different cultural settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 45 publications
1
4
0
1
Order By: Relevance
“…As indicated by the negative associations of EE with symptom remission and functional restoration, EE could hinder clinical recovery. This finding is consistent with those of previous studies showing that EE was positively related to the number of relapses and the duration of rehospitalizations among psychiatric patients (Cechnicki et al, 2013; Domínguez-Martínez et al, 2014; Hooley et al, 1986; Miklowitz et al, 1988) and that EE reduction programs were effective in improving clinical stability and functional competence among psychiatric patients (Leff et al, 1982; Tomás et al, 2012). Given the inhibitory effects of EE on clinical recovery, practitioners should engage patients from high-EE families in treatments that help mitigate their psychiatric symptoms and improve their adaptive functioning.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…As indicated by the negative associations of EE with symptom remission and functional restoration, EE could hinder clinical recovery. This finding is consistent with those of previous studies showing that EE was positively related to the number of relapses and the duration of rehospitalizations among psychiatric patients (Cechnicki et al, 2013; Domínguez-Martínez et al, 2014; Hooley et al, 1986; Miklowitz et al, 1988) and that EE reduction programs were effective in improving clinical stability and functional competence among psychiatric patients (Leff et al, 1982; Tomás et al, 2012). Given the inhibitory effects of EE on clinical recovery, practitioners should engage patients from high-EE families in treatments that help mitigate their psychiatric symptoms and improve their adaptive functioning.…”
Section: Discussionsupporting
confidence: 93%
“…Cross-sectional studies have found that EE is linked to more relapses, longer hospitalizations, and more severe psychiatric symptoms and functional impairments among psychiatric patients (Cechnicki, Bielańska, Hanuszkiewicz, & Daren, 2013; Domínguez-Martínez, Medina-Pradas, Kwapil, & Barrantes-Vidal, 2014; Hooley, Orley, & Teasdale, 1986; Miklowitz, Goldstein, Nuechterlein, Snyder, & Mintz, 1988). Further, intervention studies have demonstrated that patients whose family members receive EE-related psychoeducation have better clinical outcomes (Leff, Kuipers, Berkowitz, Eberlein-Vries, & Sturgeon, 1982; Tomás et al, 2012).…”
Section: Expressed Emotion and Recoverymentioning
confidence: 99%
“…There is evidence to suggest that maternal criticism and warmth are dynamic aspects of the family environment amenable to intervention. Interventions have shown positive effects on EE in caregivers of several populations with heightened internalizing and externalizing problems, including individuals with schizophrenia (Lenior, Dingemans, Schene, Hart, & Linszen, 2002; Tomas et al, 2011), depressive disorders (Katsuki et al, 2011), and eating disorders (Sepulveda et al, 2010). Several scholars have argued that similar interventions may effectively reduce parental EE within families of children and adults with ASD (Greenberg et al, 2006; Hastings & Lloyd, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…However, it is important to acknowledge that some studies not included in this review because they did not include any physical health components might have achieved physical health improvement in carers. An example of this being a study that used the Family Work Model reported better quality of life in carers’ physical health, although the model focused primarily on addressing expressed emotions (Tomás et al, 2012). It is possible that improving psychological health and reducing caregiving burden may have some impact in improving carers’ physical health, which is supported by the close associations found between these factors (Poon et al, 2015; Thunyadee et al, 2015).…”
Section: Discussion and Applications To Practicementioning
confidence: 99%